BDNF receptor cleavage : relevance for Alzheimer’s disease pathophysiology - Fonseca-Gomes, João Filipe (2020)
Alzheimer’s Disease (AD) is a chronic and progressive neurodegenerative disease, being the most common form of dementia worldwide (60-70% of all cases). AD is considered a protein misfolding disease and the accumulation of amyloid-beta (Aβ) peptide in the brain is considered one of the main hallmarks of this disease. Accumulatoin of this peptide induces a multiplicity of neurotoxic consequences, which ultimately supports the neuronal death, tightly associated with AD pathophysiology. In line with these alterations promoted by Aβ peptide also alterations in the signaling mediated by the brain-derived neurotrophic factor (BDNF) have been described. BDNF actions on neuronal survival, differentiation and plasticity are mediated by the activation of its full-length receptor (TrkB-FL). The impairment of BDNF signalling in AD might be explained by the decreased protein levels of BDNF and TrkB-FL, together with an increase of truncated TrkB isoforms (TrkB-Tc), which act as negative modulators of BDNF effects. In the last years, we have been establishing a direct relationship between Aβ peptide accumulation and TrkB-FL cleavage. Indeed, we observed, using different experimental approaches and several biological resources, that Aβ peptide, due to a dysfunctional activation of extrasynaptic N-methyl-D-aspartate receptor (eNMDAr), leads to an increase of intracellular calcium. As a consequence, calpains became overactivated and cleave TrkB-FL receptor, forming a new truncated receptor (TrkB-T’) and an intracellular fragment (TrkB-ICD), promoting the loss of BDNF signalling previously reported in the literature. Therefore, the Aβ-triggered cleavage of TrkB-FL receptor might be a strong contributor to neurodegeneration and to an overall loss of neuroprotection in AD patients. This project aimed i) to deeply assess TrkB-ICD fragmentimpact upon normal physiology, ii) to evaluate TrkB-FL cleavage in human post-mortem brain samples from AD patients, and iii) to develop and test a newly developed drug to prevent TrkB-FL cleavage. By the transfection of primary neurons, its was possible to investigate the role of TrkB-ICD. We found that TrkB-ICD i) is a stable fragment, ii) has tyrosine kinase activity and iii) accumulates in the nucleus, indicating a possible propagation of the initial Aβ toxicity. Furthermore, TrkB-ICD overexpression, by viral transduction of primary neuronal cultures with pFCK-CamKII-TrkB-ICD-IRESZsGreen induced an up-regulation of genes involved in neurotransmitter activity and in neural development, promoting in paralel a down-regulation of genes involved in chromosome structure stability and telomere organization, as analysed by whole trancriptome analysis (next generation sequencing). Remarkably, through in vivo intrahippocampal injection of the same viral particles in wild-type (WT) animals (C57BL/6, 12 weeks), we observed a disruption in recognition memory (Novel Object Recognition test) in TrkB-ICD-expressing animals. TrkB-ICD overexpression did not affect locomotion and anxiety-like behaviour. Intriguingly, we observed an increase in long-term potentiation magnitude, the molecular basis for learning and memory, recorded from hippocampal slices of TrkB-ICD-expressing-animals. This evidence is apparently not in line with the cognitive impairments detected in vivo. This discrepancy may indicate that TrkB-ICD promotes a dysfunctional increase in synaptic plasticity and could underlie, at least in part, the memory impairment well-described in AD patients. Regarding TrkB-FL cleavage validation in human brain samples, we used post-mortem inferior temporal cortical samples from human AD patients at different stages of disease severity. Results indicate that, over AD progression, TrkB-FL protein levels decreased, while TrkB-ICD protein levels increased. We must reinforce that this set of data is of an extreme importance, since it validated the enhancement of TrkB-FL cleavage in human patients diagnosed with AD. Finally, following 2D and 3D structural predictions, we designed a new compound to prevent TrkB-FL cleavage. Importantly, we validated the action of the new compound as a strategy that prevents TrkB-FL cleavage, through in vitro and ex vivo studies. Importantly, in addition to molecular studies, functional assays reinforced the potential therapeutic value of the new compound, since the prevention of TrkB-FL cleavage avoided the loss of BDNF function upon LTP and neurotransmitter release. Due to the promising collected data, this compound has a provisional patent application filled in UK. In summary, the data here presented i) indicates that TrkBICD might contribute or aggravate the Aβ toxicity, ii) validates the exacerbation of TrkB-FL cleavage in AD human brain samples, and iii) demonstrates a possible therapeutic value for our new created compound designed to prevent TrkB-FL cleavage. Interestingly, TrkB-FL cleavage was already described in other pathologies, including epilepsy, stroke and ischemia. Therefore, it should be indicated that the evidences described in this work might be transposed to other diseases where excitotoxicy plays a central role.